AGO recommendations for the diagnosis and treatment of patients with early breast cancer: update 2022 - Ditsch, Nina; Wöcke, Achim; Untch, Michael; Jackisch, Christian; Albert, Ute-Susann; Banys-Paluchowski, Maggie; Bauerfeind, Ingo; Blohmer, Jens-Uwe; Budach, Wilfried; Dall, Peter; Fallenberg, Eva Maria; Fasching, Peter A.; et al. (Breast care, 2022)
The AGO (Arbeitsgemeinschaft Gynäkologische Onkologie, German Gynecological Oncology Group) Task Force on Diagnosis and Treatment of Breast Cancer as an interdisciplinary team consists of specialists from gynecological oncology, pathology, diagnostic radiology, medical oncology, and radiation oncology with a special focus on breast cancer.
Gesehen am 14.11.2023